Teaching, the Legal Education and Carl Rogers Assumptions: A Case Study in a Private University - Leal, Leonardo José Peixoto (2015)
This article proposes to evaluate in a critical view of the legal education in Brazil, from Case Study at a private University of Fortaleza. It is important issue, given the continued criticism about the low quality of teaching of legal science in addition to the large number of entry of difficulty with trained professionals in the market and also the high failure rates in the orderof examination lawyers and tenders, existing today a new vision called "legal education crisis" in Brazil. According to Carl Rogers (1972), the main role of the teacher is not only to teach but to help the student to learn. This idea has been legitimized internationally since the publication of the UNESCO Report (Delors, 1998), when it pointed out that "learning to know" constitutes one of the pillars of contemporary education. Rogers (1972), in the 1960s,  drew up a list of 10 assumptions implicit deeply rooted among teachers, paradigms that should be addressed by teachers The methodology used was literature and documents with a qualitative approach in the case like an argument from Case Study, considering the Master in Law and the experiences of the Monitoring and Group Study Program. It concludes that the critical evaluation is important in the formation of the legal profession, because the legal education needs to renew itself, from a teaching practice centered learning.